Delayed Failure after Endoscopic Staple Repair of an Anterior Spine Surgery Related Pharyngeal Diverticulum. (16th December 2013) - Al-Khudari, Samer; Succar, Eric; Standring, Robert; Khadra, Helmi; Ghanem, Tamer; Gardner, Glendon M.
Abstract : We present a rare complication of endoscopic staple repair of a pharyngeal diverticulum related to prior anterior cervical spine surgery. A 70-year-old male developed a symptomatic pharyngeal diverticulum 2 years after an anterior cervical fusion that was repaired via endoscopic stapler-assisted diverticulectomy. He initially had improvement of his symptoms after the stapler-assisted approach. Three years later, the patient presented with dysphagia and was found to have erosion of the cervical hardware into the pharyngeal lumen at the site of the prior repair. We present the first reported case of late hardware erosion into a pharyngeal diverticulum after endoscopic stapler repair.